2018
DOI: 10.1097/hjh.0000000000001741
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of MRI-derived adipose tissue measurements and anthropometric markers with prevalent hypertension in the community

Abstract: MRI-derived adipose tissue measurements perform similarly in identifying prevalent hypertension compared with anthropometric markers. Especially, TAT, VAT and PAT as well as WHtR and waist circumference were highly correlated with prevalent hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…However, whether there were sex differences in the relationship between these simple markers and hypertension together with directly measured VAT and SAT has not been examined in the Chinese population. Our findings demonstrated that WC was independently associated with an increased risk of hypertension in both sexes, which was consistent with Lorbeer et al's result indicating that WC was also the most strongly associated marker of the anthropometric marker group [7]. Furthermore, WC was also significantly associated with hypertension in women but had a borderline correlation in men when adjusted for VAT and SAT.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, whether there were sex differences in the relationship between these simple markers and hypertension together with directly measured VAT and SAT has not been examined in the Chinese population. Our findings demonstrated that WC was independently associated with an increased risk of hypertension in both sexes, which was consistent with Lorbeer et al's result indicating that WC was also the most strongly associated marker of the anthropometric marker group [7]. Furthermore, WC was also significantly associated with hypertension in women but had a borderline correlation in men when adjusted for VAT and SAT.…”
Section: Discussionsupporting
confidence: 92%
“…Indirect adiposity indices such as BMI, waist circumference (WC), and hip circumference (HC) are usually used as surrogate markers because these anthropometric measures are more correlated with direct adiposity measures such as VAT or SAT [7]. Increases in WC, HC, and BMI were also associated with higher risks of hypertension [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quantification of adipose tissue compartments, volume-interpolated 3D in/opposed-phase VIBE-Dixon sequence was performed and adipose tissues were segmented semi-automatically 28,29 . SAT was quantified from cardiac apex to femoral head and VAT was quantified from diaphragm to femoral head; Total adipose tissue was defined as the sum of SAT and VAT, all indicated in liter.…”
Section: Methodsmentioning
confidence: 99%
“…The isotropic VIBE-Dixon sequence was also acquired for the analysis and evaluation of abdominal adipose tissue compartments and adipose tissues were segmented semi-automatically, as described previously [14,17,18]. Thus, volumetric assessment of the subcutaneous adipose tissue (SAT) from the femoral head to the cardiac apex and visceral adipose tissue (VAT) from the femoral head to the cardiac apex was quantified by a fat selective tomogram using an in-house algorithm (based on Matlab R2013a).…”
Section: Assessment Of Adipose Tissue Compartmentsmentioning
confidence: 99%